Otoritas Pemerintah dalam Menetapkan Awal Bulan Qamariyah (Studi terhadap Pandangan Dosen IAIN Pontianak) - Dahlia Haliah Ma’u (Khatulistiwa, 2016)
The aim of this study was to describe and explain the perception of IAIN Pontianak lecturers about government authority in establishing the beginning of Qamariyah month. Writer investigated this issue because the determination of the beginning of Qamariyah is often debatable. This issue was not only discussed by the academics, but also common people. The participation of academic’s thought related to the establishment of the beginning of Qamariyah will be worth if it was described in the form of scientific study. This study used qualitative approach with descriptive method. Using this method, writer can describe various kind of information related to the object of the study. This study also used the source of main data or primary data that is lecturers of IAIN Pontianak. The secondary data source consists of documents and articles related to this study. The results of this study showed that the perception of IAIN Pontianak lecturers about government authority in establishing the beginning of Qamariyah month can be classified into two categories: agree and disagree. For the first category, agree is divided into two parts: people who agree with a provision and agree without provision. People who agree with a provision mean that the government act as ulil amri (leader), hence, all the provisions must be followed by the society. Then people who do not agree argue that the Indonesian grounding state was not religion, but based on the 1945 constitutions, hence, the decision was decided by each party. There are some implications of the establishment of the beginning of Qamariyah by the government. First, it can minimize the differences and conflicts among Muslims in Indonesia generally and among the lecturers of IAIN particularly. Second, it can maintain the unity of Muslims in Indonesia and the brotherhood among lecturers. Third, the government will be authoritative and politisize the Qamariyah calendar. Fourth, as the tool to unite all Muslims because it is come from the binding decision accordingly the unity among the people will be established. Furthermore, the factor that influences the differences among lecturers of IAIN consists of: affiliated organizations, educational background, and the level of understanding about hisab and ru’yah.